Public Perceptions of Cross-Sex Vascularized Composite Allotransplantation. Issue 6 (December 2020) - Mills, Emily C.; Alfonso, Allyson R.; Wolfe, Erin M.; Park, Jenn J.; Sweeney, Guillermo Najera; Hoffman, Alexandra F.; Felsenheld, Julia H.; Sosin, Michael; Ramly, Elie P.; Rodriguez, Eduardo D.
Abstract : Background: Cross-sex vascularized composite allotransplantation has been performed in cadaveric facial transplantation and clinical extremity transplantation. Understanding the challenge of appropriate donor-recipient matching, this study sought to characterize the public's perception of cross-sex vascularized composite allotransplantation. Methods: Participants were surveyed in New York City. Data collected included demographics and willingness to donate vascularized composite allografts (VCAs) of various types. Similar questions were asked in the context of same-sex and cross-sex donation. Results: A total of 101 participants (male: 56.4%; age ⩽35 years: 62.4%) were surveyed. The majority expressed willingness to donate to recipients of a different sex (hand: 78.2%, face: 56.4%, penis or uterus: 69.3%, lower limb: 81.2%, abdominal wall: 80.2%, larynx: 81.2%, and solid organs: 85.2%). Among VCAs, willingness to donate facial allografts was significantly different in same-sex versus cross-sex contexts (64.4% vs 56.4%; P = 0.008). Participants were also significantly more likely to donate VCAs to same-sex recipients on behalf of themselves versus loved ones ( P < 0.05). There was significantly lower willingness to receive cross-sex versus same-sex facial ( P = 0.022) and genital allografts ( P = 0.022). Education on the preservation of recipient masculinity or femininity in cross-sex facial transplantation increased participants' willingness to receive a cross-sex face transplant from 56.4% to 71.3% ( P = 0.001). Conclusions: This study highlights the urban public's acceptance of VCA donation or reception regardless of sex mismatch. There is increased willingness to receive a cross-sex face transplant after education, highlighting opportunities for future focused interventions to increase public awareness and ultimately the donor pool. Abstract : Supplemental digital content is available in the text.